Fabrication And Properties Of Silver Based Multiwall Carbon Nanotube Composite Prepared By Spark Plasma Sintering Method - Lis M. (Archives of Metallurgy and Materials, 2015)
The paper presents results of investigations of the obtained nanocomposite materials based on silver with addition of multiwall carbon nanotubes. The powder of carbon nanotubes content from 0.1 to 3 wt. % was produced by application of powder metallurgy methods, through mixing and high-energetic milling, and also chemical methods. Modification of carbon nanotubes included electroless deposition of silver particles on the carbon nanotube active surfaces and chemical reduction with strong reducing agent – sodium borohydride (NaBH4). The obtained powder mixtures were consolidated by SPS – Spark Plasma Sintering method. The formed composites were subjected to tests of relative density, electrical conductivity and electro-erosion properties. Detailed examinations of the structure with application of X-ray microanalysis, with consideration of carbon nanotubes distribution, were also carried out. The effect of manufacturing methods on properties of the obtained composites was observed.